Infection risk in sterile operative procedures - Tacconelli, Evelina; Mutters, Nico T. (Deutsches Ärzteblatt, 2016)
Background - The main objective of hospital hygiene and infection prevention is to protect patients from preventable nosocomial infections. It was recently stated that the proper goal should be for zero infection rates in sterile surgical procedures. In this article, we attempt to determine whether this demand is supported by the available literature. - - Methods - We systematically searched the Medline and EMBASE databases for studies published in the last 10 years on the efficacy of infection control measures and carried out a meta-analysis according to the PRISMA tool. We used the following search terms: “aseptic surgery,” “intervention,” “surgical site infection,” “nosocomial infection,” “intervention,” and “prevention.” - - Results - 2277 articles were retrieved, of which 204 were acquired in full text and analyzed. The quantitative analysis included 7 prospective cohort studies on the reduction of nosocomial infection rates after aseptic surgery. The measures used included training sessions, antibiotic prophylaxis, and operative-site disinfection and cleaning techniques. These interventions succeeded in reducing postoperative wound infections (relative risk (RR] 0.99 [0.98; 1.00]). Subgroup analyses on antibiotic prophylaxis (RR 0.99 [0.98; 1.01]) and non-controlled trials (RR 0.97 [0.92; 1.02]) revealed small, insignificant effects. - - Conclusion - A multimodal approach with the participation of specialists from various disciplines can further reduce the rate of postoperative infection. A reduction to zero is not realistic and is not supported by available evidence.